2008
DOI: 10.1038/sj.bjp.0707640
|View full text |Cite
|
Sign up to set email alerts
|

Role of complement C5a in mechanical inflammatory hypernociception: potential use of C5a receptor antagonists to control inflammatory pain

Abstract: Background and purpose: C5a, a complement activation product, exhibits a broad spectrum of inflammatory activities particularly neutrophil chemoattraction. Herein, the role of C5a in the genesis of inflammatory hypernociception was investigated in rats and mice using the specific C5a receptor antagonist PMX53 (AcF-[OP(D-Cha)WR]). Experimental approach: Mechanical hypernociception was evaluated with a modification of the Randall-Selitto test in rats and electronic pressure meter paw test in mice. Cytokines were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
67
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(70 citation statements)
references
References 60 publications
(92 reference statements)
2
67
1
Order By: Relevance
“…PMX53 does reduce inflammatory hypernociception, however, and therefore has the potential to relieve inflammatory pain. 21 These data suggest the hypothesis that a c5a antagonist could provide necessary analgesia during (stress) fracture healing, without compromising the remodeling processes of bone healing.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…PMX53 does reduce inflammatory hypernociception, however, and therefore has the potential to relieve inflammatory pain. 21 These data suggest the hypothesis that a c5a antagonist could provide necessary analgesia during (stress) fracture healing, without compromising the remodeling processes of bone healing.…”
Section: Discussionmentioning
confidence: 90%
“…20 It is a potent inflammatory mediator and is involved in the progression of immuno-inflammatory conditions such as rheumatoid arthritis, inflammatory bowel disease, asthma, and psoriasis. 21 A C5a receptor antagonist, PMX53, has been trialled as a NSAID, demonstrating potent inhibition of C5a mediated neutrophil chemotaxis, phagocytosis and leukocyte release of inflammatory cytokines. 22,23 Is has been used to target the complement system and has shown positive therapeutic effects in animal models of inflammatory arthritis.…”
mentioning
confidence: 99%
“…Emerging evidences suggest that C5a, the anaphylatoxin produced by complement activation, has potent nociceptive activity in several models of inflammatory and neuropathic pain by interacting with its selective receptor C5aR (7,8). C5aR belongs to the class A subfamily of the seven-transmembrane (TM) G protein-coupled receptors (GPCR) (9) and is widely expressed in immune cells, including neutrophils (polymorphonuclear cells, PMN), monocytes, microglia, and in nonimmune cells, including neurons in the CNS and dorsal root ganglia (10,11).…”
mentioning
confidence: 99%
“…In animals, LTB 4 -induced hyperalgesia was inhibited by leukocyte depletion (Levine et al, 1984). Recently, it has been demonstrated that neutrophils are important for the hyperalgesia induced by carrageenin, zymosan and antigen-induced inflammation by further producing nociceptive mediators including LTB 4 and PGE 2 (Cunha et al, 2008b;Guerrero et al, 2008;Ting et al, 2008;Verri et al, 2009). On the other hand, it has also been described that neutrophils can reduce hyperalgesia by releasing opioids at the local inflammatory site (Cunha & Verri, 2006;Rittner et al, 2006).…”
Section: Discussionmentioning
confidence: 99%